Validation Study of Tumor Invasive Thickness for Postoperative Prognosis in 110 Patients Who Underwent Pancreatoduodenectomy for Distal Cholangiocarcinoma at a Single Institution. (May 2019) - Zhao, Yang; Nakanishi, Yoshitsugu; Ogino, Mariko; Oba, Mitsunobu; Okamura, Keisuke; Tsuchikawa, Takahiro; Nakamura, Toru; Noji, Takehiro; Asano, Toshimichi; Tanaka, Kimitaka; Hosoi, Hayato; Nakayama, Tomohide; et al.
Abstract : The pT classification of the 8th American Joint Committee on Cancer (AJCC) for distal cholangiocarcinoma (DCC) is classified according to depth of invasion (DOI), which is the distance from the basal lamina to the most deeply advanced tumor cells. The Nagoya group proposed a new T classification for DCC based on invasive tumor thickness (ITT), which is the maximal vertical distance of the invasive cancer component (the ITT grade). In this study, we aimed to validate the ITT grade for the next pT classification of DCC in 110 patients. ITT could be measured in all patients, but DOI could only be measured in 62 (56%) patients. According to ITT grade, patients were classified into grades A to D, as follows: grade A, ITT <1 mm (n=9); grade B, ITT 1 mm or more but <5 mm (n=35); grade C, ITT 5 mm or more but <10 mm (n=40); and grade D, ITT 10 mm or greater (n=26). The median overall survival times in patients with ITT grades A, B, C, and D were 12.8, 5.7, 3.7, and 2.0 years, respectively. ITT grade could discriminate postoperative survivals between grades. On multivariate analysis, ITT grade, regional lymph node metastasis, and distant metastasis were selected as independent prognostic factors. In summary, our results showed that ITT grade was a suitable alternative to DOI for pT classification in the next edition of the AJCC for DCC.